Síntese estereosseletiva de feromônios monoinsaturados de lepidópteros através de reações de acoplamento com organolítio - Vanderlei, José Maurício de Lima (2014)
Population growth and consumption improvement as caused an increased demand for nutrients of a better quality. As a result mono cropping has become a powerful tool in order to obtain current requirements. In order to acquire large agricultural areas, deforestation of native wood lands has increased and consequently eliminated the natural habitat of predators thus allowing proliferation of certain species that have become pests. Amongst these species are those who belong to Lepidoptera genera, which is the second largest group of insects including approximately 150 000 identified species and 120 families, becoming one of the main agriculture pests as they infest crop such as: corn, soy, sugarcane, cotton etc. Recently, a new pest Helicoverpa armigera (Hübner, 1805) has emerged in Brazilian crops causing economical loses of roughly R$ 2 billion. Its importance is due to the fact of being a generalist pest, which is infesting crops of cotton, corn, sorghum, wheat and tomato, decreasing the productivity and increasing expenses on pesticides. The emergence of this pest in Brazilian crops has enforced the necessity of new pesticides. Despite this, advances of pest and disease control should be in alliance with environmental and natural resources in matters of productivity, product quality, inputs and resources, adding value in health protection, environmental and food safety systems. This requires continuous innovation through scientific and technological knowledge in particularly pest control. Currently in Brazil the usage of pheromones as a control method against pests in included in agribusiness. In majority of cases, pest control is conducted through the usage of pesticides, however, monitoring would be a more economical approach and it would also decrease risk of toxic residues on fruits. Regarding the synthesis, the 10-bromodecan-1-ol (1) and 8-bromodecan-1-ol (2) were protected with dihydropyran (DHP) catalyzed by some crystals of p-toluene sulfonic acid (pTSA)in tetrahydrofuran (THF). The metalation was performed using nbutyllithium (n-BuLi) to generate the acetylide an ion from 1-hexyne 7 which react with1-(Tetrahydro-2′-pyranyloxy)-10-bromodecane 4 across from a second order nucleophilic substitution mechanism (SN2). This step yelds 1-(Tetrahydro-2′-pyranyloxy) -11-hexadecyne 8. In ordertoobtain1- (Tetrahydro-2′-pyranyloxy)-9-hexadecyne 9 and 1-(Tetrahydro-2′-pyranyloxy)-9-tetradecynne 10 was used the same coupling methodology. The ethers 8, 9 and 10 were subsequently deprotected to yield 11-Hexadecyn-1-ol 11, 9-Hexadecyn-1-ol 12 and 9-tetradecyn-1-ol 13. The compounds (Z)-11-Hexadecen-1-ol 14, (Z)-9-Hexadecen-1-ol 15 and (Z)-9-tetradecen-1-ol 16 were prepared by stereoselective reduction using Lindlar catalyst (Pd/CaCO3, 5%), the (Z)-11-hexadecenyl acetate 17 was prepared by acetylation using acetic anhydride and pyridine. Oxidation of the alcohol 15 with pyridinium chlorochromate (PCC) in dichloromethane gave the (Z)-9-hexadecenal aldehyde. The products of reductions, oxidation and acetilation are componentes of the pheromonal mixtures of the followings pecies: Heliothis virescens (Fabricius, 1777); Spodoptera frugiperda (Smith,1797); Plutella xylostella (Linnaeus, 1758); Helicoverpa armígera (Hübner, 1805); Helicoverpa zea (Boddie, 1850); Spodoptera eridania (Cramer).